Study on Diversity and Potency of Some Macro Mushroom at Gunung Gede Pangrango National Park - Ivan Permana Putra; Muhammad Aldi Nasrullah; Tiara Aulia Dinindaputri (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2019)
Biodiversity is a valuable asset which should be preserved and protected. Gunung Gede Pangrango National Park (GGPNP) is one of the conservation areas with a high level of biodiversity in Indonesia. Currently, mushroom diversity in GGPNP is rarely reported. Inventory of mushroom diversity is the first step of actions to maintaining germplasm and maximizing its potential usagein the future. In this paper, we explain how to use macroscopic characters to help identification of macro mushroom. The fungi collected from GGPNP were 19 species and 14 genera, including: Armillaria sp. 1, Armillaria sp. 2, Auricularia sp., Daedalea sp. 1, Daedalea sp. 2, Fomitopsis sp., Ganoderma sp. 1, Ganoderma sp. 2, Marasmius sp., Microporus sp. 1, Microporus sp. 2,Mycena sp., Phellinus sp., Polyporus sp., Rigidoporus sp., Russula sp., Sistotrema sp., Xylaria sp. 1, and Xylaria sp. 2. These mushroom could be potentially used as food and medicinal source.